Integrating Historical Knowledge with Civic Competences in Pre-University Education in Albania - Mehmeti, Ndriçim; Mehmeti, Nevila; Sallata, Ilir (European Journal of Social Science Education and Research, 2025)
This study analyzes the integration of historical knowledge with civic competences in pre-university education in Albania, evaluating the role of teaching in developing students’ democratic understanding and active participation. Using a mixed-methods research approach (quantitative and qualitative methods), data were collected through two structured questionnaires administered in March 2025, involving 627 students from lower and upper secondary education, as well as 76 history teachers from both urban and rural areas. The data analysis showed that although students demonstrate good levels of knowledge about democracy and civic values, their practical involvement remains limited, especially in school decision-making and community activities. The study also highlights differences between urban and rural schools in teaching approaches, digital resources, and institutional support. The findings emphasize the need for strengthened teacher professional development, deeper integration of historical content with civic competences, and the creation of a more open classroom dialogue to reinforce young people’s democratic participation. The recommendations aim to guide educational policies toward improving teaching methods, empowering teachers, and enhancing the role of the school as a space for civic development.